IMPACT OF SUPPORT PRICE AND FERTILIZER OFFTAKE ON RICE PRODUCTION AND WHEAT ACREAGE IN NWFP, PAKISTAN - M. Niamatullah; K. U. Zaman; M. A. Khan (Journal of Animal and Plant Sciences, 2010)
The present study is attempted to measure the significant contribution of price factor (support price) and non-price factor (fertilizer offtake) towards rice production and wheat acreage responses in NWFP, Pakistan by employing Nerlovian adjustment model through ordinary least square estimation technique over a period of time (1975-76 to 2007-08). 1st aspect of findings suggest that support price has strong bearing on rice production (P<0.05) and fertilizer offtake has attained significant relationship with rice production (P<0.10). The announcement of support prices had certainly strong bearing on rice production in NWFP. In view of production response of rice, the short run and long run support price elasticities as well as short and long run fertilizer offtake elasticities were found sizeable with low divergence. 2nd aspect of findings suggest that fertilizer offtake has shown remarkable influence over wheat acreage (P<0.10). Hence the issue of nutrient deficiency was overcome due to balanced use of fertilizer offtake especially NPK had played a crucial role in achieving enhanced rice production and wheat acreage in NWFP.
Keywords: Support price; fertilizer offtake; acreage.